2007
DOI: 10.1007/s00441-006-0372-4
|View full text |Cite
|
Sign up to set email alerts
|

A simple cell motility assay demonstrates differential motility of human periodontal ligament fibroblasts, gingival fibroblasts, and pre-osteoblasts

Abstract: During periodontal regeneration, multiple cell types can invade the wound site, thereby leading to repair. Cell motility requires interactions mediated by integrin receptors for the extracellular matrix (ECM), which might be useful in guiding specific cell populations into the periodontal defect. Our data demonstrate that fibroblasts exhibit differential motility when grown on ECM proteins. Specifically, gingival fibroblasts are twice as motile as periodontal ligament fibroblasts, whereas osteoblasts are essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…It has been suggested that α1β1 and α2β1 integrins are both functional in PDL cell interactions with collagen I, and also that an additional collagen receptor may be functional (Lallier et al, 2007). In agreement with this suggestion, analysis of our antibody data showed that antibodies to α1 and α2 integrins could only partially block collagen gel contraction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It has been suggested that α1β1 and α2β1 integrins are both functional in PDL cell interactions with collagen I, and also that an additional collagen receptor may be functional (Lallier et al, 2007). In agreement with this suggestion, analysis of our antibody data showed that antibodies to α1 and α2 integrins could only partially block collagen gel contraction.…”
Section: Discussionsupporting
confidence: 91%
“…Integrins on human PDL cells have been analyzed previously (Palaiologou et al, 2001;van der Pauw et al, 2002;Takemura et al, 2006;Lallier et al, 2007). One study used antibodies to the collagen-binding integrins α1β1 and α2β1 (Lallier et al, 2007) to investigate integrin-dependent cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 C and D), showing a considerable impairment in scrape wound repair ability. To study the potential long term effect of U94/REP on the motility rate of ECs, we evaluated HUVECs' cell migration activity (18). HUVECs were treated with recombinant U94/REP (4 g/mL), and cell movement along the bottom of a tissue culture flask was recorded after 8 days.…”
Section: Hhv-6 U94/rep and Its Gene Product Affect Endothelial Cell Mmentioning
confidence: 99%